The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.1103/physrevlett.33.765
|View full text |Cite
|
Sign up to set email alerts
|

Ion Heating by the Current-Driven Electrostatic Ion-Cyclotron Instability

Abstract: We have observed and confirmed significant ion heating by the electrostatic ion-cyclotron instability in a barium plasma. We present spectroscopic evidence showing that this mechanism drastically alters the velocity distribution, demonstrating at least a highly nonlinear process and giving strong evidence for randomization of the particle motion. Experimental corroboration of a theory of Drummond and Rosenbluth is presentedWe report the direct observation of ion heating in a fully ionized barium plasma, as ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 7 publications
3
25
0
Order By: Relevance
“…Electrostatic ion-cyclotron waves are particularly well suited for perpendicular ion heating because of the resonant coupling between the fluctuating wave electric field and the ion gyromotion [Rynn et al, 1974;Dakin et al, 1976]. The notion that electrostatic ion-cyclotron waves should be present in space originates from early laboratory experiments demonstrating the relatively low excitation threshold of such waves [DMngelo and Motley, 1962], the subsequent theoretical work that provided a framework with which to understand the instability mechanism [Drummond and Rosenbluth, 1962], and the availability of free energy from parallel currents in the highly structured and nonequilibrium high-latitude ionosphere.…”
Section: Electrostatic Ion-cyclotron Wavesmentioning
confidence: 99%
“…Electrostatic ion-cyclotron waves are particularly well suited for perpendicular ion heating because of the resonant coupling between the fluctuating wave electric field and the ion gyromotion [Rynn et al, 1974;Dakin et al, 1976]. The notion that electrostatic ion-cyclotron waves should be present in space originates from early laboratory experiments demonstrating the relatively low excitation threshold of such waves [DMngelo and Motley, 1962], the subsequent theoretical work that provided a framework with which to understand the instability mechanism [Drummond and Rosenbluth, 1962], and the availability of free energy from parallel currents in the highly structured and nonequilibrium high-latitude ionosphere.…”
Section: Electrostatic Ion-cyclotron Wavesmentioning
confidence: 99%
“…The density ratio of the hot-tail ions to the bulk ions, T I & , , increases with an increase in V,. For R, = 1.0, however, it does not exceed a few percent (RYNN et al, 1974;CORRELL et al, 1977, in which the ion heating due to the instability was also reported, although the two-component structure of the energy distribution was not observed). When we increase R, up to 1.3, a clear increase of It, is observed and, for V, 5 50 V, the distribution is almost one-component Maxwellian, having the high temperature.…”
Section: Turbulent Plasmamentioning
confidence: 79%
“…Under a uniform magnetic field, the instability excited shows a frequency spectrum having a peak a little above the ion-cyclotron frequency wci/27r. This instability has been regarded as a current-driven electrostatic ion-cyclotron instability (MOTLEY and DANGELO, 1963;RYNN et al, 1974;CORRELL et al, 1975CORRELL et al, , 1977, although other mechanism for the excitation was proposed, taking into account the sheath in front of the driving target (LEVIN and KUCKES, 1966). When R, is changed for a fixed value of B at the mirror center or at the mirror points, the frequency is observed to depend only on B at the mirror point where the small driving target is set.…”
Section: Turbulent Plasmamentioning
confidence: 99%
“…5,6 The experimental results are said to be explained by the theory developed by Drummond and Rosenbluth. 1 In the usual Q-machine experiments, a positive potential is applied to a small electrode in the plasma to induce an electric current, so the electric field has not only a component along the magnetic field lines, but also a component across the magnetic field lines.…”
Section: Introductionmentioning
confidence: 99%